2008
DOI: 10.1002/ejic.200800434
|View full text |Cite
|
Sign up to set email alerts
|

1D, 2D and 3D Coordination Polymers of Aromatic Carboxylate TbIII: Structure, Thermolysis Kinetics and Fluorescence

Abstract: Reactions of TbCl 3 ·6H 2 O with aromatic acids, namely, pyridine-2,3-dicarboxylic acid (H 2 pda), isophthalic acid (H 2 ipa) and isonicotinic acid (Hina) gave rise to three new coordina-Complex 1 constructed by eight-coordinate Tb III nodes connected with completely and half-deprotonated pda and Hpda spacers is a novel 3D metal-organic architecture with nanosized hexagonal 1D channels hosting guest water, whereas complex 2 is a 2D heterometal sheet built by completely deprotonated ipa spacers bridging eight-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 47 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…2a). 49 Furthermore, according to the UV-vis absorption data, the band gap values between H 4 TBAPy and Ln-MOFs 1–3 were 2.34, 2.54, 2.54 and 2.52 eV, respectively, estimated using the Kubelka–Munk formula (Fig. S6, ESI†).…”
Section: Resultsmentioning
confidence: 98%
“…2a). 49 Furthermore, according to the UV-vis absorption data, the band gap values between H 4 TBAPy and Ln-MOFs 1–3 were 2.34, 2.54, 2.54 and 2.52 eV, respectively, estimated using the Kubelka–Munk formula (Fig. S6, ESI†).…”
Section: Resultsmentioning
confidence: 98%
“…28,29 In addition to pyridinedicarboxylic acids, the use of bifunctional pyridine-2,3-dicarboxylic acid (pydcH 2 ) as a bridging ligand to react with transition metals has been known for its diverse coordination abilities as a result of the asymmetric coordination environments of the carboxylate groups at the 2-and 3-positions of the pyridine ring that provide variable bridging and coordination modes. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Pyridine-2,3-dicarboxylic acid is remarkably attractive for its flexible and various coordination modes to construct mononuclear, dinuclear or polynuclear architecture. The deprotonated pyridinedicarboxylates (pydc 22 and pydcH 2 ) are useful tools for constructing crystalline architectures because of their proton donating and accepting capabilities for hydrogen bonding and their pyridine ring for aromatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The UV–vis, excitation, and emission spectra of Bi-TBAPy in the solid state at room temperature are shown in Figure a. The strong and broad absorption bands at 200–450 nm were attributed to the π → π* transition . Compared with that of the ligand, it is found that the broad absorption band of Bi-TBAPy is mainly from the contribution of the ligand, and a blue shift for the maximum peak position took place.…”
Section: Resultsmentioning
confidence: 98%